Pembiakan Massal Lyriomiza huidobrensis dengan Pakan Daun Kacang Babi (Vicia faba) - Suputa Suputa; Edhi Martono (Universitas Gadjah Mada, 1998)
Mass rearing of Lyriomiza huidobrensis, a relatively new leaf miner known to attack potato, was done by using Vicia faba leaf as feed. The leaf miner was able to survive well on this feed, which in the field provide the larvae with alternative host. Result of the rearing was as follows: egg stadium, 4–5 days; larval stadium, 8–9 days; pupal stadium, 12–14 days; male adult longevity, 7–32 days; female adult longevity, 13–41 days. The number of eggs deposited by an average female varied between 114 to 592, with viability of 69.93 to 97.78%, and an average daily deposit of 8–25 eggs. The most important environmental factor in this mass rearing is temperature.